Extractivism, expulsion and patriarchal violence in the transnational prostitution of Nigerian women - Delicado-Moratalla, Lydia (Filanderas, 2021)
In this essay I elaborate a theoretical framework to understand the sexual violence and the political meaning of the transnational forced prostitution of Nigerian women in Europe. I draw from the radical feminist literature and feminist geopolitics to explain the dimensions of the inherent patriarchal violence that is part of the sexual exploitation system studied in this case. I conduct an examination of the political ecology of the Niger Delta to inquire the origins of the prostituted women. This allows me to explore the structural impoverishment that is created by the extractivism in the area. All these factors catapult the expulsion dynamics. I build a dissenting critique of the «sex work» narrative that has been developed within the geographic discipline and, finally, I propose an abolicionist interpretation for research related to current prostitution.
Keywords: Prostitution; Extractivism; Feminist Geopolitics; Nigerian Women; Abolicionism